2017
DOI: 10.1051/0004-6361/201628363
|View full text |Cite
|
Sign up to set email alerts
|

Improved model of the triple system V746 Cassiopeiae that has a bipolar magnetic field associated with the tertiary

Abstract: V746Cas is known to be a triple system composed of a close binary with an alternatively reported period of either 25 d .4 or 27 d .8 and a distant third component in a 170 yr (62000 d) orbit. The object was also reported to exhibit multiperiodic light variations with periods from 0 d .83 to 2 d .50, on the basis of which it was classified as a slowly pulsating B star. Interest in further investigation of this system was raised by the recent detection of a variable magnetic field. Analysing spectra from four in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…McSwain et al (2007) obtained updated RV measurements on this spectroscopic binary and settled on a best-fit period of 25.4176 days after combining all data sets. Harmanec et al (2018) acquired additional velocities and determined several spectroscopic solutions that confirmed that the broad-lined component is the primary of the 25-day orbit. We acquired five new RVs of the broad-lined component (v i sin 137 = km s −1 ) with the 2 m AST, which are consistent with the 25-day SPEFO orbit of Harmanec et al (2018, Table 3).…”
Section: Hd 1976mentioning
confidence: 94%
“…McSwain et al (2007) obtained updated RV measurements on this spectroscopic binary and settled on a best-fit period of 25.4176 days after combining all data sets. Harmanec et al (2018) acquired additional velocities and determined several spectroscopic solutions that confirmed that the broad-lined component is the primary of the 25-day orbit. We acquired five new RVs of the broad-lined component (v i sin 137 = km s −1 ) with the 2 m AST, which are consistent with the 25-day SPEFO orbit of Harmanec et al (2018, Table 3).…”
Section: Hd 1976mentioning
confidence: 94%